PENGAWASAN TERHADAP PRODUK HUKUM DAERAH DI ERA REFORMASI - Santoso Budi NU (Wacana Hukum, 2011)
Abstrak : Controlling towards legal product based on UU No. 32 year 2004 covers reventive aspect and represive aspect. Preventive aspect refers to Perda before used in regency level, a governor is indirectly called as authority while in province level, the authority is domestic minister. Represive aspect refers to Perda after used and as the authority is Mahkamah Agung. Keywords: Pengawasan, Produk Hukum Daerah dan Era Reformasi